1973
DOI: 10.1111/j.1365-2141.1973.tb01661.x
|View full text |Cite
|
Sign up to set email alerts
|

A Method for the Measurement of Platelet Adhesiveness by Use of Dialysis Membranes in a Test‐Cell

Abstract: Summary. As part of a study of the thrombogenic properties of dialysis membranes a test‐cell has been devised in which the retention of platelets in the presence of different membranes can be measured. This provides a test for platelet adhesiveness which in certain aspects is more sensitive and reproducible than a glass bead column technique. The normal range for platelet adhesiveness was found to be 31 ± 9% using whole blood and 19 ± 3% using platelet‐rich plasma. The platelet adhesiveness value was largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1973
1973
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The glass bead column method of testing platelet adhesiveness is related to the release ofADP and other substances from red cells which have been disrupted. In contrast, retention of platelets in the membrane test cell is apparently independent of haematocrit or exogenous ADP release (Lindsay et al, 1973). Since PGE2 may exert its effect on platelets by inhibiting ADP release, the glass bead method may swamp the effect of PGE2 on platelets by releasing large amounts of aggregating substances from the red cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The glass bead column method of testing platelet adhesiveness is related to the release ofADP and other substances from red cells which have been disrupted. In contrast, retention of platelets in the membrane test cell is apparently independent of haematocrit or exogenous ADP release (Lindsay et al, 1973). Since PGE2 may exert its effect on platelets by inhibiting ADP release, the glass bead method may swamp the effect of PGE2 on platelets by releasing large amounts of aggregating substances from the red cells.…”
Section: Discussionmentioning
confidence: 99%
“…Platelet adhesiveness to a cellophane membrane in a test cell was measured by the method of Lindsay, Prentice, Ferguson, Muir, and McNicol (1973). In this method, 10 ml of citrated blood is passed over a cellophane membrane and platelet counts are performed on the blood before and after being passed through the cell to calculate the retention of platelets.…”
Section: Methodsmentioning
confidence: 99%
“…A number of methods are now available for the study of platelet adhesion as an isolated event [4548]. Lyman and his co-workers [49][50][51] have studied platelet adhesion to artificial surfaces under flow conditions. These studies were extended by others [52,53].…”
Section: Methods For Study Of Platelet Adhesionmentioning
confidence: 99%
“…Depending on the methods used for in vitro measurement of platelet adhesiveness, aspirin sometimes is shown to reduce [7,30,106,128,152,153,174,177,201,224,256,269,279] and sometimes to have no effect on [18,20,136,168,187,219,243,276] platelet adherence to surfaces. Thus a number of studies have demonstrated that platelet retention in glass bead columns [201,224,256], or platelet adhesiveness to glass coverslips [174] or to connective tissue fibers [106,279], using undiluted or diluted [174] platelet-rich plasma, is reduced after aspirin, whereas methods using whole blood usually showed normal adhesiveness after aspirin [18,276].…”
Section: Aspirin Effect On Platelet Adhesionmentioning
confidence: 99%